Gerakan Sosial Politik Alimin bin Prawirodirdjo Dalam Partai Komunis Indonesia (PKI) - Mahadika, Alam (Journal of Applied Transintegration Paradigm, 2023)
This research article narrates Alimin bin Prawirodirdjo's social-political movement within the Indonesian Communist Party. This research article conveys Alimin bin Prawirodirdjo's social-political movement, which was rarely discussed and silenced after 1965. Even many young people today do not know the figure of the struggle. Alimin was also one of the leaders of the Indonesian independence movement and an Indonesian communist sculptor who became a national hero. This study uses a qualitative approach using historical methods. This research focuses on libraries and documents related to the discussion using the historical process. The indicators of this research discussed in the debate are Alimin bin Prawirodirdjo's life history, the movement in the Indonesian Communist Party, being a member of the Constituent Assembly, their determination as a National Hero, and the narrative of Alimin's work in socialism thought.